Core-middle-periphery network model for China banking system - Chen, Na; Liu, Jianguo; Chen, Yihui; Tu, Ding; Ou, Yang; Jiang, Mingzhu (Frontiers in Physics, 2022)
Interbank system could be mapped by the network model to generate the structure properties of evolution dynamics. In this paper, by taking into account the transaction data of China interbank pledged repo market, we empirically investigate the evolution properties of interbank network from 2008 to 2019 where the banks and lending relationships are set as the nodes and links. By introducing the Middle layer into the Core-Periphery (CP) model, we present the Core-Middle-Periphery (CMP) model where the nodes belonging to the core layer are fully connected and the ones belonging to the Middle layer connect the core and periphery layer. Comparing with the traditional CP model, the total error e_(C-M-P) of the CMP could be decreased by 79%, and the average stability probability W ̅ of the layer subset increased from 47% (W ̅_c) and 63% (W ̅_p) in CP model to 77.5% (W ̅_c), 69.1%(W ̅_m)and 68.5%(W ̅_p) in the CMP model respectively. This work is helpful for deeply understanding the evolution property of interbank market.